2019
DOI: 10.1002/ajpa.23883
|View full text |Cite
|
Sign up to set email alerts
|

Diet and adult age‐at‐death among mobile foragers: A synthesis of bioarcheological methods

Abstract: Objectives: The research explores whether the combined study of cortical bone histology, bone morphology, and dietary stable isotopes can expand insights into past human health and adaptations, particularly dietary sufficiency and life span. Materials and methods: Midthoracic rib cortices from 54 South African Late Holocene adult skeletons (28 M, 24 F, two sex undetermined) are assessed by transmitted-light microscopy for cross-sectional area measurements, osteon area (On.Ar), osteon population density, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 113 publications
0
12
0
Order By: Relevance
“…Age‐at‐death was estimated by dental eruption, epiphyseal fusion, cranial suture closure, changes to the sternal rib ends and os‐coxae. Age‐at‐death for leaner populations of shorter stature and mobile south African foragers is often underestimated (Merritt, ; Pfeiffer, Cameron, Sealy, & Beresheim, ), therefore, it is acknowledged that the age may be underestimated in this study. Individuals were classified broadly as young (20–35 years), middle‐aged (35–50 years), old (>50 years) adults, or as ‘unknown adult’.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Age‐at‐death was estimated by dental eruption, epiphyseal fusion, cranial suture closure, changes to the sternal rib ends and os‐coxae. Age‐at‐death for leaner populations of shorter stature and mobile south African foragers is often underestimated (Merritt, ; Pfeiffer, Cameron, Sealy, & Beresheim, ), therefore, it is acknowledged that the age may be underestimated in this study. Individuals were classified broadly as young (20–35 years), middle‐aged (35–50 years), old (>50 years) adults, or as ‘unknown adult’.…”
Section: Methodsmentioning
confidence: 90%
“…Other studies on archaeological assemblages of Khoesan have shown similar results (Botha & Steyn, ). These data show unsuitability of contemporary morphological sex and age methods, highlighting the need for developing population‐specific sex and age estimation methods (Kurki, Pfeiffer, & Stynder, ; Pfeiffer et al, ; Pfeiffer & Harrington, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The acquisition of CT images, extraction of cross-sections at each level, the setting of thresholds for the definition of cortical bone, and the acquisition of quantitative values were performed without any modifications from the protocol established for the modern Japanese population, indicating that the method is applicable to the measurement of archaic human bones and that the values obtained can be directly compared with those of the modern Japanese population. Femoral morphology is important not only for its clinical significance in predicting fracture risk [ 5 8 ] but also in terms of predicting the living environment [ 12 14 ]. However, as our previous studies have shown, the trends of age-related changes were different for diaphyseal peripheral border length and thickness of cortical bone.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that bone morphology correlated with mechanical functions by comparing these quantitative values to the findings of a finite element analysis using a 3D model constructed from CT images [ 11 ]. In addition to the estimation of disease risk, bone morphology has been considered to reflect the living environment of adults [ 12 14 ] based on Wolff's law that bone morphology changes to adapt to a given load [ 15 ]. Therefore, differences in the curvature of the femoral diaphysis among populations and differences in femoral morphology among various groups of archaic human bones have been analyzed to investigate the living environment [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%